Differential Alcohol Use Disparities by Sexual Identity and Behavior Among High School Students. (9th December 2020) - Phillips II, Gregory; Wang, Xinzi; Ruprecht, Megan M; Felt, Dylan; McCuskey, David; Stephens, Reno; Perez-Bill, Esrea; Beach, Lauren B
Abstract: Aims: Sexual minority youth (SMY) use alcohol at disproportionate rates compared to their heterosexual peers. However, sexual orientation is multidimensional. Analyzing alcohol use disparities only by one dimension of sexual orientation may result in critical disparities being obscured. Methods: Data from state and local versions of the Youth Risk Behavior Survey were pooled (2009–2017), resulting in a large, diverse sample ( n  = 201, 671). Multivariable logistic regression models were used to analyze associations between sexual identity/sexual behavior and three alcohol use outcomes among sexually active youth: age at first drink, binge drinking and current drinking. Results: SMY, when categorized by sexual identity and sexual behavior, reported greater alcohol use than their heterosexual peers, though the magnitude of these disparities varied by subgroup. Both those who identified as bisexual and those who reported sexual behavior with both males and females reported the greatest levels of alcohol use. Decomposition analysis revealed that youth whose reported sexual behavior was not aligned with stereotypical behavioral expectations based on their sexual identity had higher odds of current drinking and drinking before 13 years as compared to other youth. Conclusions: Results highlight the need to incorporate multiple methods of sexual orientation measurement into substance use research. Interventions based solely on identity, rather than both identity and behavior, may not be sufficient; targeted research into the causes of alcohol use disparities is needed, especially for bisexual youth, youth whose sexual behavior and sexual identity are not stereotypically aligned, and youth who report a sexual identity of 'not sure.' Abstract : Short Summary: SMY use alcohol at higher rates; the magnitude of these disparities differs by sexual identity and sexual behavior. Bisexuals and youth who had sex with males and females reported the most alcohol use. Sexual behavior that was unaligned with expectations based on sexual identity was associated with drinking.